From Barbusse to Lemaitre: The Evolution of Experience - Nancy Sloan Goldberg (Anglica. An International Journal of English Studies)
Direct witness and thoughtful meditation are core values of content and form in the canon of French Great War fiction and were established from the earliest narratives in 1914. Moral authority and ownership of the truth were both the privilege of soldier-writers like Barbusse and Dorgelès, who also sought insightful meaning in their direct experience. Their works remain “in collective memory” and continue to be published, read, and analysed (Grabes). With the passage of time, the gaps in insights and memory of direct witness were filled by fiction in the works of canonical post-memory writers (Rigney). The rediscovery and reappraisal of disparate elements of the war by historians and non-canonical genre writers restored value to some of these objects, such as executions and the reintegration of veterans into society, that had “fall[en] out of frames of attention” (Assmann). Crime fiction novels set during the Great War, by virtue of their non-canonical status as genre fiction, were not restrained by acknowledged and often depreciatory imperatives of form and content. Unencumbered by these canonical constraints, the works of crime fiction writers tell a “counter-history,” thus transferring a proscribed and obfuscated subject to the public sphere (Assmann).